The clinical value of neutrophil-to-lymphocyte and platelet-to-lymphocyte ratios for predicting the occurrence of pneumonia, the need for mechanical ventilation, and death in cardiac patients - Anna Konopka; Małgorzata Stępień-Wojno; Witold Śmigielski (Folia Cardiologica)
INTRODUCTION: The neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are strong markers of a poor prognosis in many diseases. AIM: The main purpose of the study was to check the relationship between the NLR and PLR and pneumonia, the necessity of mechanical ventilation (MV), and death in patients being treated in the intensive cardiac care unit (ICCU) due to severe cardiovascular diseases. MATERIAL AND METHODS: In 279 patients enrolled in the study, the NLR and PLR were calculated within 24 hours of admission to the ICCU and on the day of initiation of MV or on the 3rd day of hospitalization. RESULTS: In the second measurement the median (Q1–Q3) for the NLR in patients with pneumonia was 10.49 (6.53–19.29), 11.98 (7.33–21.17) in patients with MV, and 14.58 (7.30–27.10) in those who died. All values that were significant in univariable logistic regression were analyzed in multivariable logistic regression. The NLR assessed in the second measurement was a predictor of pneumonia with an odds ratio (OR) of 2.3 and 95% confidence interval (CI) of 1.6–3.2, with a p-value < 0.001. The NLR in the same measurement was also a risk factor of MV (OR 7.62, CI 2.76–21.06, p < 0.001) and death (OR 2.57, CI 1.59–4.18, p < 0.001). CONCLUSIONS: NLR and PLR values on admission to the ICCU were significantly elevated in patients who developed pneumonia and those who required MV or died, in comparison to patients without these adverse events. The NLR obtained on the 3rd day of hospitalization or on the day of MV start was an independent risk factor for pneumonia, the need for MV, and death.